Is hemi-thyroidectomy adequate in low risk differentiated thyroid cancer? - Benjamin, Justin (World J Nucl Med, 2019)
In low-risk differentiated thyroid carcinoma (LRDTC), appropriate surgical procedure in terms of hemi/total thyroidectomy (TT) has been an area of debate. The aim was to determine whether in LRDTC patients, hemithyroidectomy would be an adequate treatment, determine incidence of disease in contralateral lobe and evaluate the effect of radioactive iodine ablation (RAIA). Retrospective study was done from 2008 to 2014 at a single institution. Preoperative ultrasound (USG) and histopathology reports of all LRDTC patients following total/completion thyroidectomy were recorded. Details of postthyroidectomy, thyroid whole body scan, and stimulated serum thyroglobulin (sTg) levels were also documented and results analyzed. A total of 114/562 patients met inclusion criteria. Of these, 25/114 (22%) underwent hemithyroidectomy followed by a completion thyroidectomy while remaining 89/114 (78%) underwent TT initially. Preoperative USG detected single-lobe involvement in 44 patients; however, among them, histopathology revealed bilateral lobe disease in 17 (38.6%). There was a significant fall of sTg level following RAIA as compared to that before RAIA in T1b-T2 (P = 0.009 and 0.012, respectively). Median follow-up was 2 years (range: 1–7 years) with no distant metastasis or deaths recorded till 2017, except for one local recurrence 4 years after RAIA. In conclusion, the role of TT in LRDTC patients is important as 46% of patients were found to have tumor in contralateral lobe as well. Significant fall in sTg levels following RAIA justifies RAIA of remnant lobe even in LRDTC (T > 1a). It facilitates early detection of recurrence when sTg alone is used for follow-up.